Bermuda : Assessment of the Supervision and Regulation of the Financial Sector-Volume II-Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents key findings of the Detailed Assessment of the Observance of Standards and Codes in the Financial Sector of Bermuda. The small number of licensed deposit-taking institutions in Bermuda are part of the broader financial intermediation sector. Typically, some 50 percent to 60 percent of the banks' income is fee based. The value of client assets and the volume of their activities are the main generators of this income. Efforts to reduce employee and occupancy costs that reflect the high cost of doing business on the island are continuing.